Behavioural and emotional functioning of adolescents with mild intellectual disability: Perspectives from home and school - Marsh, Nigel V.*; Ng, Siau H (Asociacion Científica de Psicología y Educación (ACIPE)., 2017)
This study examined the frequency and severity of behavioural and emotional disturbances in adolescents with mild intellectual disability. The 50 adolescents, aged between 12 and 16 years, attended a special school in Singapore. Information on the adolescents’ functioning was obtained from their parent/primary carer and their class teacher, who both completed the relevant version of the Developmental Behaviour Checklist. The results showed that, in addition to difficulties related to their intellectual disability, 22% to 27% of students displayed significant behavioural and emotional disturbances. Disruptive/Antisocial behaviours were the most frequently reported problems. But communication disturbances were reported as being the most severe problems. Carers and teachers reported the same pattern in the relative frequencies of the different types of problems. However, primary carers consistently reported a higher frequency than teachers for all types of problems. Implications of these findings for the consistent management of the adolescents’ challenging behaviour are discussed